Relationships Among Biomass, Carbon, and Microfibril Angle in Young Shorea spp. (Dipterocarpaceae) in Indonesia - Reinardus Liborius Cabuy; Descarlo Worabai; Dony Aristone Djitmau; Sophan Chhin (Universitas Gadjah Mada, 2023)
Indonesia, particularly the island of Java, is dominated by a number of Shorea tree species (Dipterocarpaceae). Trees of the genus have been utilized for various practices, and they play a fundamental role in managing the stability of tropical forests. This study was carried out to understand the relationships between biomass and microfibril angle in Shorea spp. growing in West Java, where Shorea spp., are abundant. A total of 35 young trees belonging to 5 species were studied. The average age of these trees was 9 years, but in general there was a wide variation in tree diameter and total height. On average, biomass was the highest in S. leprosura and the lowest in S. palembanica. The lowest average microfibril angles (MFAs) were found in S. leprosura and S. mecistopteryx. The regression relationship between biomass and diameter was strong with an R2 value of 0.85, while the strength of the relationship between MFA and diameter was weaker (R2 = 0.195). In general, the MFA degree decreased with increased biomass accumulation Shorea species, which affects tree resistance to environmental variables and competitiveness in Indonesian tropical forests.